Frequency of EGFR Mutations in Patients with Lung Adenocarcinoma: Comparative Study between Private and Public Healthcare Centers - Rafael, Rodríguez-Cid Jeronimo; Guillermo, Martos-Rami?rez; Vanessa, Garci?a-Montes; Rafael, Flores-Mariñelarena Rodrigo; Diana, Bonilla-Molina; Olivares-Beltra?, (Archives of Clinical and Medical Case Reports, 2020)
Purpose: The present study aims to describe the differences in the prevalence of EGFR mutation of lung adenocarcinoma between private and public healthcare institutions. Methods: This was a descriptive, observational, retrospective, multicenter study with confirmed diagnosis of non-small cell lung cancer, adenocarcinoma subtype, distributed between two private practice centers and one public healthcare institution. After a pathology review to determine whether there was enough tumor tissue to make a molecular biology study, mutations were determined using real-time PCR for EGFR tyrosine-kinase domain gene. Results: After exclusions a total of 328 patients results for the final analysis. Two hundred thirty-five patients (71.64%) attended a public healthcare institution and ninety-three patients (28.35%) to a private healthcare institution (Table 1). From the public healthcare institution, 113 (34.45%) patients had a positive EGFR mutation, while only 27 patients (8.23%) from the private healthcare institution were positive for an EGFR mutation. When comparing the total number of patients in the study, this difference was statistically significant when comparing public versus private hospitals (p=0.002). Conclusion: We found that there is a statistically significant difference between the frequency of EGFR mutations between populations attending public and private healthcare institutions, probably related to ethnic differences between populations. Despite what has been reported in the present study, these conclusions cannot be generalized and further investigation is needed.